The Study of Feminism in the Novel of the Choice Mother God Works Rizka Azizah - Azgha, Roditha; Wardarita, Ratu; Wardiah, Dessy (Jurnal Pendidikan Tambusai, 2021)
Feminism is one type of literary theory that is used to examine or analyze problems related to women in literary works. As for the formulation of the problem in this research, what are the forms of gender injustice contained innovel Ibu selectedgod Rizka Azizah'sby. This study aims to determine the forms of gender injustice innovel Ibu selectedgod Rizka Azizah'sby. The research method used is descriptive qualitative method. The technique used is literature study. The data source is the novel Ibu Selected God by Rizka Azizah, the research data is a manifestation of existing gender injustices, namely: marginalization, subordination, stereotypes, violence, workload, which reflects the feminism studynovel ibutuhan of Rizka Azizah'sTerbaikby Rizka Azizah. Based on the results of data analysis, this research can conclude that the novel Ibu Selected by God is appropriate for the study of female gender feminism, which in the novel discusses gender injustice against women.